Tensile properties of the hip joint ligaments are largely variable and age-dependent – An in-vitro analysis in an age range of 14–93 years. Issue 14 (3rd October 2016) - Schleifenbaum, Stefan; Prietzel, Torsten; Hädrich, Carsten; Möbius, Robert; Sichting, Freddy; Hammer, Niels
Abstract: Introduction: Hip joint stability is maintained by the surrounding ligaments, muscles, and the atmospheric pressure exerted via these structures. It is unclear whether the ligaments are capable of preventing dislocation solely due to their tensile properties, and to what extent they undergo age-related changes. This study aimed to obtain stress–strain data of the hip ligaments over a large age range. Methods: Stress–strain data of the iliofemoral (IL), ischiofemoral (IS) and pubofemoral ligament (PF) were obtained from cadavers ranging between 14 and 93 years using a highly standardized setting. Maximum strains were compared to the distances required for dislocation. Results: Elastic modulus was 24.4 (IL), 22.4 (IS) and 24.9 N/mm 2 (PF) respectively. Maximum strain was 84.5%, 86.1%, 72.4% and ultimate stress 10.0, 7.7 and 6.5 N/mm 2 for the IL, IS and PF respectively. None of these values varied significantly between ligaments or sides. The IS' elastic modulus was higher and maximum strain lower in males. Lower elastic moduli of the PF and higher maximum strains for the IS and PF were revealed in the ≥55 compared to the <55 population. Maximum strain exceeded the dislocation distance of the IS without external hip joint rotation in females, and of the IS and cranial IL under external rotation in both genders. Discussion: Tensile and failure load properties of the hip joint ligaments are largely variable. The IS and PF change age-dependently. Though the hip ligaments contribute to hip stability, the IS and cranial IL may not prevent dislocation due to their elasticity.